Pengaruh Pendidikan, Pelatihan dan Motivasi terhadap Produktivitas Kerja Pegawai di Rumah Sakit Sumber Hurip - Bella Putri Madani; Budiharto; Zahera Mega Utama (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the effect of education, training and motivation on employee productivity partially and simultaneously at Sumber Hurip Hospital. The method used in this research is descriptive method, with the type of correlation study. The approach used in this research is a quantitative approach. In this study the researcher took a sample using the probability sampling method is simple random sampling. Simple random sampling is taking sample members from a population that is carried out randomly without regard to the strata in that population. The population in this study were Sumber Hurip Hospital employees with a total of 320 employees. The data analysis technique used is validity test, reliability test, descriptive analysis and inferential statistical data analysis. The results of the study show that education has no effect on employee work productivity at Sumber Hurip Hospital. Training has an effect on Employee Work Productivity at Sumber Hurip Hospital. Motivation affects Employee Work Productivity at Sumber Hurip Hospital. Education, training and motivation have a simultaneous effect on Employee Work Productivity at Sumber Hurip Hospital.